Gambaran Penanaman Kemandirian pada Anak Usia Dini oleh Orang Tua dalam Keluarga - Nadia Safitri; Setiawati Setiawati; Wirdatul Aini (Universitas Negeri Padang, 2018)
This research is motivated by the high independence of children, it is suspected a relationship with the cultivation of independence given to the child. The purpose of this study illustrates the cultivation of independence in children by parents in the family in Jorong Giri Maju Pasaman Barat Regency, through the cultivation of child self-confidence, planting the child's habituation, and planting communications with children. This research is quantitative descriptive research. Parents of children aged five to six years are the population and sample in this study. The data collection techniques used are questionnaires and data collection tool is a questionnaire and data analysis techniques using percentage calculations. The results of the study found that the cultivation of independence through cultivation of self-confidence implemented by parents is categorized well, the cultivation of self-reliance through habituation conducted by parents is categorized very well, and the cultivation of self-reliance through the cultivation of communication with children by parents is categorized very well. These three aspects of research greatly affect the independence of children.